THE ROLE OF PERSUASIVE DIALOGUE IN THE NEGOTIATION OF THE SALE OF GOODS AT SIMPUR CENTER, BANDAR LAMPUNG CITY - Dewi, Ponita; Maja, Meri Andani; Hakiki, Virgiana Mahar (Universitas Sang Bumi Ruwa Jurai, 2023)
This study discusses the role of persuasive dialogue in negotiating the sale of goods at the Simpur Center in Bandar Lampung City. This shopping center has a significant role in meeting consumer needs and in the context of intense competition, the ability to conduct effective sales negotiations becomes important. This study uses a qualitative approach with the case study method to explore a deep understanding of how persuasive dialogue contributes to the outcome of sales negotiations. The main findings of this study include persuasive dialogue strategies used by sellers, customizing messages according to buyer profiles, managing rejection, and building customer relationships. This study shows that the seller's ability to use persuasive dialogue influences the success of sales negotiations. Tailoring messages based on local preferences and culture, as well as being able to overcome resistance with relevant solutions, also contribute to successful negotiations. Furthermore, this study emphasizes the importance of understanding local culture in persuasive dialogue, because adaptation to cultural values can strengthen communication. Persuasive dialogue plays a central role in negotiating the sale of goods at the Simpur Center in Bandar Lampung City. In a competitive environment, product knowledge, tailored persuasive dialogue strategies and the ability to manage rejection wisely are all important factors in achieving success in sales. In closing, suggestions are given to improve the seller's ability to apply effective persuasive dialogue in order to achieve success in the sales negotiation process.